Computer-Assisted Surgery Using 3D Printed Saw Guides for Acute Correction of Antebrachial Angular Limb Deformities in Dogs - Worth, Andrew J.; Crosse, Katherine R.; Kersley, Andrew (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to report the use of custom saw guides produced using computed tomographic imaging (CT), computer simulation and three-dimensional (3D) printing to aid surgical correction of antebrachial deformities in six dogs.Materials and Methods Antebrachial limb deformities in four small, and two large, breed dogs (seven limbs) were surgically corrected by a radial closing wedge ostectomy and ulnar osteotomy. The location and orientation of the wedge ostectomy were determined using CT data, computer-assisted planning and production of a saw guide in plastic using a 3D printer. At surgery, the guide was clamped to the surface of the radius and used to direct the oscillating saw blade. The resultant ostectomy was closed and stabilized with a bone plate.Results Five limbs healed without complications. One limb was re-operated due to a poorly resolved rotational component of the deformity. One limb required additional stabilisation with external fixation due to screw loosening. The owners of five dogs completed a Canine Orthopedic Index survey at a follow-up period of 37 to 81 months. The median preoperative score was 3.5 and the median postoperative score was 1, representing an overall positive effect of surgery. Radiographically, 5/7 limbs were corrected in the frontal plane (2/7 were under-corrected). Similarly, 5/7 limbs were corrected in the sagittal plane, and 2/7 were over-corrected in the sagittal place.Conclusions Computer-aided design and rapid prototyping technologies can be used to create saw guides to simplify one-stage corrective osteotomies of the antebrachium using internal fixation in dogs. Despite the encouraging results, accurate correction of rotational deformity was problematic and this aspect requires further development.
Keywords: angular limb deformity; three-dimensional printing; rapid prototyping; saw guide; computed tomography